Not-for-profit audit committee best practices - Ruppel, Warren (Hoboken, N.J. : John Wiley & Sons, 2006)
Since not-for-profits are not required to comply with Sarbanes-Oxley, they have the advantage of being able to select from alternative ways of functioning. Not-for-Profit Audit Committee Best Practices helps audit committee members select from various best practices to tailor the functioning to their particular circumstances.
NOT-FOR-PROFIT AUDIT COMMITTEE BEST PRACTICES; About the Author; Contents; Preface; Chapter 1: Background and Regulatory Issues; Chapter 2: Establishing an Audit Committee and Determining Its Charter; Chapter 3: Responsibilities of Internal Control over Financial Reporting; Chapter 4: Understanding and Addressing the Risks of Fraud; Chapter 5: Defining the Role of the Internal Audit Function; Chapter 6: Establishing an Effective Whistleblower Program; Chapter 7: Audit Committee's Relationship with the Independent Auditor; Chapter 8: An Audit Committee Action Plan; Index.
Includes index.
Print version record.
John Wiley and Sons
Keywords: Nonprofit organizations -- Auditing; BUSINESS & ECONOMICS -- Accounting -- Managerial; Nonprofit organizations -- Auditing